Phytase in diets with crude protein levels for commercial layers - Pereira, Adriana Aparecida; Junqueira, Otto Mack [UNESP]; Griep, Dirceu Neutzling; Lima, Dorgival Morais De; Sgavioli, Sarah [UNESP]; Moraes, Socorro Da Silva (Editora da Universidade Estadual de Maringá - EDUEM, 2017)
The aim of this study was to evaluate the action of the phytase enzyme in diets formulated with variations in the crude protein content on performance and egg quality of commercial layers. A total of 336 commercial layers were housed at eight birds per cage in a 3 × 2 factorial arrangement with seven replicates. Treatments consisted of four crude-protein levels (17, 15, and 13%) and two enzyme levels (0 and 500 FTU kg-1 diet), distributed in a completely randomized design. Feed intake, egg production, feed conversion per dozen eggs and per kilogram, egg weight and mass, specific gravity, eggshell thickness, and Haugh unit were measured over five 28-day periods. The performance of commercial layers fed the diet containing 13% crude protein worsened, irrespective of phytase addition. However, at 15% crude protein, phytase inclusion did not affect feed conversion or egg weight. Inclusion of phytase leads to equal egg-quality and performance results at the dietary crude protein levels of 17 and 15%. The crude protein content of 13%, with or without phytase, is not recommended for the diet of brown-egg layers.

Objetivou-se avaliar a ação da enzima fitase em rações formuladas com variação na proteína bruta sobre o desempenho e a qualidade de ovos de poedeiras comerciais. Foram alojadas 336 poedeiras comerciais, em esquema fatorial 3 x 2, com sete repetições e oito aves em cada gaiola. Os tratamentos constituíram de três níveis de proteína bruta (17, 15 e 13%) e dois níveis da enzima fitase (0 e 500 FTU kg-1 ração), distribuídos em delineamento inteiramente casualizado. Durante cinco períodos, de 28 dias cada, foram avaliados o consumo de ração, a produção de ovos, a conversão alimentar por dúzia e por quilograma, o peso e a massa de ovos, a gravidade específica, a espessura de casca e a unidade Haugh. Constatou-se piora no desempenho das poedeiras comerciais alimentadas com 13% de proteína bruta na ração, independente da adição da fitase. Porém, em 15% de proteína bruta, a inclusão da fitase não afetou a conversão alimentar e o peso dos ovos das aves. A inclusão da fitase proporciona resultados de qualidade de ovos e desempenho iguais para os níveis de 17 e 15% de proteína bruta na ração. Não se recomenda o nível de 13% de proteína bruta, com ou sem fitase, na ração de poedeiras semipesadas.
Fitase em rações com níveis de proteína bruta para poedeiras comerciais
Keywords: phosphorus; chicken; nitrogen; eggs; fósforo; aves; nitrogênio; ovos